PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN PASER - Rizkyah Nur Ayuni; Erni Susanti; Achmad Syahruddin (Paser Institute Management and Busines, 2023)
This research aims to evaluate the influence of Organizational Culture (X) on Employee Performance (Y) at the Paser Regency Manpower and Transmigration Service. Organizational Culture Variables (X) consist of Innovation and Risk Taking (X1), Attention to Details (X2), Results Orientation (X3), People Orientation (X4), Team Orientation (X5), Aggressiveness (X6), and Stability (X7). The sample consisted of 61 employees using a saturated sampling technique. Testing the validity and reliability of the questionnaire was carried out before multiple linear regression analysis. The results show 32 valid and reliable statements. The regression equation found is Y = 0.539 + 0.507 X1 + 0.074 X2 - 0.099 X3 + 0.017 X4 - 0.001 A multiple correlation of 0.910 shows a very strong relationship between Organizational Culture and Employee Performance, with an adjusted R Square value of 80.5%. Simultaneous testing shows that overall organizational culture has a significant effect on employee performance (Fcount > Ftable, p-value < 0.05). Partial testing indicates that the variables Innovation and Risk Taking (X1), Aggressiveness (X6), and Stability (X7) have a positive effect on Employee Performance. However, the variables Attention to Details (X2), Results Orientation (X3), People Orientation (X4), and Team Orientation (X5) do not have a significant influence. Thus, the hypothesis that Aggressiveness (X6) has a dominant influence on Employee Performance is not proven.